2013
DOI: 10.1002/lsm.22198
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and acceleration of bone repair in critical‐sized rat calvarial defects using low‐level laser therapy

Abstract: Background and Objective Tissue regeneration remains a challenge for orthopedic and craniomaxillofacial surgery to treat bone loss. The use of low‐level laser therapy suggests a promise on this road with positive results for narrow defects. However, temporal and quantitative evaluations are required to understand the healing process of large injuries. The aim of this study was to investigate the repair of critical‐size bone defects in rat calvaria using a GaAlAs laser. Study Design/Materials and Methods Bone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In the two analysed periods, the animals biostimulated with the laser presented greater evidence of new bone formation and greater tissue organisation at the end of the experiment [33]. These results are consistent with the literature that indicates the positive photobiomodulatory effects of the laser in the initial phases of bone repair, when, among several events, there is a proliferation of osteoblasts and differentiation of mesenchymal cells [34,35].…”
Section: Discussionsupporting
confidence: 80%
“…In the two analysed periods, the animals biostimulated with the laser presented greater evidence of new bone formation and greater tissue organisation at the end of the experiment [33]. These results are consistent with the literature that indicates the positive photobiomodulatory effects of the laser in the initial phases of bone repair, when, among several events, there is a proliferation of osteoblasts and differentiation of mesenchymal cells [34,35].…”
Section: Discussionsupporting
confidence: 80%
“…Some studies used only one evaluation period, totaling:5 sessions 8-10 , 6 sessions 3,21 and 8 sessions 15,17 . Other studies have had two or more evaluation periods, such as: 6 and 18 sessions 18 ; 3, 6 and 9 sessions 13 ;3, 6 and 12 sessions 14 16 temporal and quantitative evaluations are required to understand the healing process of large injuries. The aim of this study was to investigate the repair of critical-size bone defects in rat calvaria using a GaAlAs laser.…”
Section: 8) Laser Application Schedule (Days) and Treatment Sessionsmentioning
confidence: 99%
“…There were no pig/sheep study models found within our inclusion criteria methods. Regarding defect localization, three different regions employed in the studies analyzed: calvaria 3,16,18,20 constituting a promising strategy to produce bone tissue healing. Objective: the aim of the present study was to investigate the in vivo performance of PBM using an experimental model of cranial bone defect in rats.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations